The Role of Music Education in the Development of Creativity in Children: Aspects of Piano Teaching - Sokolova Fotima Kamilovna (Research Parks Publishing LLC, 2024)
This scientific article explores the significant role of musical education, specifically piano instruction, in fostering the creative abilities of children. The study delves into various aspects of piano education, considering its impact on cognitive development, emotional expression, and overall creative potential. The research draws upon a comprehensive literature review and empirical evidence to highlight the multifaceted benefits of piano instruction on the creative capacities of young minds.